2023
DOI: 10.14507/epaa.31.7993
|View full text |Cite
|
Sign up to set email alerts
|

Re-centering civil rights in the reauthorization of ESEA: An equitable, ecological, evidence-based framework

Elizabeth H. DeBray,
Kara S. Finnigan,
Janel George
et al.

Abstract: This article considers the reauthorization of the Elementary and Secondary Education Act (ESEA) in light of current educational inequities and the impact of the pandemic. The reauthorization presents an opportunity to center equity and justice and revitalize the civil rights aspects of the law. The authors review recent studies about the myriad ways the COVID-19 pandemic affected students, teachers and school systems and situates the reauthorization within the broader political context, including federal aid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Policy researchers Elizabeth DeBray and Janelle Scott and I, along with legal scholar Janel George, recently discussed the importance of focusing on both student and teacher well-being as policymakers tackle the long-overdue reauthorization of the ESEA (DeBray et al, 2022(DeBray et al, , 2023. We noted that Recognizing and addressing the mental health impacts of the pandemic and long-standing unattended issues of inequality that have been magnified by it, will be critical to helping students thrive because unaddressed mental health issues, alongside a failure to adopt policies and practices that can give students and teachers necessary supports, can compromise future well-being and education trajectories for students.…”
Section: Policy Targets To Support Flourishingmentioning
confidence: 99%
See 1 more Smart Citation
“…Policy researchers Elizabeth DeBray and Janelle Scott and I, along with legal scholar Janel George, recently discussed the importance of focusing on both student and teacher well-being as policymakers tackle the long-overdue reauthorization of the ESEA (DeBray et al, 2022(DeBray et al, , 2023. We noted that Recognizing and addressing the mental health impacts of the pandemic and long-standing unattended issues of inequality that have been magnified by it, will be critical to helping students thrive because unaddressed mental health issues, alongside a failure to adopt policies and practices that can give students and teachers necessary supports, can compromise future well-being and education trajectories for students.…”
Section: Policy Targets To Support Flourishingmentioning
confidence: 99%
“…We noted that Recognizing and addressing the mental health impacts of the pandemic and long-standing unattended issues of inequality that have been magnified by it, will be critical to helping students thrive because unaddressed mental health issues, alongside a failure to adopt policies and practices that can give students and teachers necessary supports, can compromise future well-being and education trajectories for students. (DeBray et al, 2023) We suggested that components of the Every Students Succeed Act (ESSA), which is the latest version of ESEA, be more directly grounded in an 'equitable, evidence-based, ecosystem' framework which centers the health and the socioemotional well-being of students and educators and considers and addresses the consequences of systemic structural and environmental factors that interact with the experiences of these individuals and groups in their communities and schools. An important step is leveraging connections within the ESSA titles themselves, such that health and mental health may be incorporated at the local level.…”
Section: Policy Targets To Support Flourishingmentioning
confidence: 99%